DNA methylation and the APP gene: dietary influences in the context of Alzheimer’s disease—a mini review - Silva-Martínez, G. A.; Cervantes-Montelongo, J. A.; Tristán-Flores, F. E.; de la Rocha, C. (Frontiers in Nutrition, 2026)
One of the main pathological features of Alzheimer’s disease (AD) is the accumulation of amyloid β (Aβ) peptides, which is encoded by the amyloid precursor protein (APP) gene. The etiology of sporadic AD (non-familial) remains largely unknown, and genetic mutations explain only about 5–10% of cases. Epigenetic alterations, such as DNA methylation, have been proposed as mechanisms contributing to the overproduction of Aβ, which is associated with aggregation. Differences in methylation in the APP gene has been reported in certain brain regions and blood samples from individuals with AD. Dietary components and natural compounds such as fatty acids, methionine, and folate have been associated with differential methylation and may represent potential therapeutic or preventive strategies for AD. This mini-review discusses available evidence on how specific dietary factors and natural compounds may influence DNA methylation of the APP gene revealing promising directions for nutrition-oriented prevention strategies.